ANALISIS PENDAPATAN TERHADAP ASET DAN LIABILITAS RUMAH SAKIT WISMA RINI PRINGSEWU PASCA PELAKSANAAN PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) - Yohanes Suharsana; Bartolomeus Fredy Nugroho (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Health service for the time being into an industry that is in demand by employers in view of theimportance of public health. This make the government should help facilitate people to obtain health carewithout being complicated by the issue of cost is premises with program BPJS. Hospitals should be able toincrease its revenue through service by leveraging the asset and liabilities in order to compete with otherhospitals.This rearch aimed to analyze how the influence of incomeon asset and liability with the programBPJS in Wisma Rini Hospital. The analytical method used is the method of financial Statements usingcommon size ratio of profit and loss and balance sheet common Results of the study was to show that theincome greatly affects assets and liability with the program BPJS in Wisma Rini Hospital.